Specific Features in Plant Cover Recovery Along the Routes of Linear Structures in Northwestern Siberia (Osobennosti Protsessa Vosstanovleniia Rastitel'nogo Pokrova na Trassakh Lineinykh Sooruzhenii Severa Zapadnoi Sibiri) - Moskalenko,N. G. (1976)
This report presents observations made in the lacustrine-alluvial plain in the Nadym-Kazymskiy interfluve in the northern taiga subzone. Destruction of plant cover in regions of permafrost during economic development of land causes change in the soil temperature conditions, intensification or weakening of freezing and thawing processes, and development of cryogenic processes. In this connection, observation of plant cover recovery along routes of linear structures, hindering intensification of thawing and freezing and development of erosion and thermal Karst processes, is of certain practical significance. (Author) Trans. of Geograficheskoe Obshchestvo SSSR, Izvestiya (USSR) v107 n1 p62-67 Jan-Feb 75.